2022
DOI: 10.1055/a-1965-3472
|View full text |Cite
|
Sign up to set email alerts
|

Intensivverlegungen in der COVID-19-Pandemie – eine Analyse aus einem landesweit koordinierten Intensivverlegungssystem

Abstract: Zusammenfassung Zusammenfassung Diese Analyse untersucht den Einfluss der COVID-19-Pandemie auf ein landesweites Intensivverlegungssystem. Material und Methoden Um die Auswirkungen der COVID-19-Intensivtransporte zu analysieren, wurden retrospektiv 2 17-monatige Betrachtungszeiträume ausgewählt. Ergebnisse Im Untersuchungszeitraum wurden 5291 Intensivtransporte durchgeführt. Von diesen Transporten waren 525 Intensivtransporte mit COVID-19, wovon 474 (90,3%) per ITW und 51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…As the emergency ambulance (RTW) was the first choice transport vehicle, it reinforces the assumption that patients were significantly sicker. Similar to our data, an analysis of intensive care transports (COVID-19 and non-COVID-19 patients) from Germany demonstrated that COVID-19 patients had increased disease severity and intensive care requirements 23 . More time was also needed during patient handover at the arrival hospital, as SARS-CoV-2- patients usually had a longer and complicated medical history.…”
Section: Discussionsupporting
confidence: 88%
“…As the emergency ambulance (RTW) was the first choice transport vehicle, it reinforces the assumption that patients were significantly sicker. Similar to our data, an analysis of intensive care transports (COVID-19 and non-COVID-19 patients) from Germany demonstrated that COVID-19 patients had increased disease severity and intensive care requirements 23 . More time was also needed during patient handover at the arrival hospital, as SARS-CoV-2- patients usually had a longer and complicated medical history.…”
Section: Discussionsupporting
confidence: 88%